Activated wood surface and functionalized cellulose co-building strong chemical wood bonding performance. (1st April 2023) - Liu, Tongda; Du, Guanben; Wu, Yingchen; Liu, Chang; Yang, Hongxing; Ni, Kelu; Yin, Chunyan; Ran, Xin; Gao, Wei; Yang, Long
Abstract: Herein, an activated wood surface rich in CHO groups was constructed by spraying a sodium periodate aqueous solution on a natural wood surface. Besides, microcrystalline cellulose was functionalized to obtain aminated cellulose, which was dissolved in an aqueous solution and used as a specific adhesive. Subsequently, an ultrastrong wood bonding interface was co-constructed with the activated wood surface and aminated cellulose, which was formed by a chemical covalent reaction between aldehyde groups at the activated wood interface and amino groups on aminated cellulose. The dry, hot-water, and boiling-water lap shear strengths of the plywood specimens were 1.47, 1.07, and 1.08 MPa, respectively. The boiling-water strength of the plywood made from the activated wood surface achieved increased to 1.08 MPa from 0 MPa of the plywood constructed on the nonactivated wood surface. The chemical crosslinking reaction and bonding mechanism between the adhesive and activated wood surface were clarified by density functional theory calculations, attenuated total reflectance–Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The results showed that chemical bonding (aminal NCN and imine CN) at the bonding interface played an important part in improving the water resistance and bonding strength. This work provides new concepts for designing durable and moisture-resistant wood products. Graphical abstract: Schematic diagram for the design and development of superstrong wood bonding via chemical bond between activated wood surface and aminated cellulose. Unlabelled Image